Enthalpy relaxation of selenium observed by fast scanning calorimetry - Pilař Radim; Honcová Pavla; Schulz G.; Schick C.; Málek Jiří (Elsevier Science BV, 2015)
The enthalpy relaxation of amorphous selenium was studied using fast scanning calorimeter, where the heating/cooling rates up to 10,000 K s(-1) were used. The observed relaxation effects were compared with the measurements done by classical differential scanning calorimetry. Description of the data and prediction of the relaxation behavior using the Tool-Narayanaswamy-Moynihan model is discussed.
Entalpická relaxace selenu studovaná rychlou skenovací kalorimetrií
Keywords: Relaxation; Selenium; Fast scanning calorimetry; Fictive temperature; TNM model; relaxace; selen; rychlá skenovací kalorimetrie; fiktivní teplota; TNM model